Observing coaches` leadership behaviours: the development of the coach leadership assessment system (CLAS) - Turnnidge, J.; Côté, J. (Measurement in Physical Education and Exercise Science, 2019)
The purpose of the present study was to develop an observational coding system that examines coaches` leadership behaviours in sport. Drawing from an integration of the dimensions emphasized within the full-range leadership model, and particularly, transformational leadership (TFL), the Coach Leadership Assessment System (CLAS) was designed to examine coaches` real-time leadership behaviours. Behavioural categories were developed through an iterative combination of literature review, qualitative interviews, and video observation. The CLAS consists of five higher-order dimensions: transformational, transactional, neutral, laissez-faire, and toxic coaching, which assess coaches` leadership across 18 distinct behavioural categories. Overall, results provided preliminary support for the reliability and validity of this instrument. The CLAS provides a detailed and contextualized account of coaches` leadership behaviours in sport and may have important implications for theory development and applied practice.